CHARCOAL ANALYSIS and the VEGETATIONAL EVOLUTION of NORTH-WEST PORTUGAL - FIGUEIRAL, I (Oxford Journal of Archaeology, 1993)
Summary: The palaeoenvironment of north-west Portugal is investigated from the late Bronze Age to Roman times. This research is based on the analysis of charcoal from seven archaeological sites. the results contain important information for a better understanding of the vegetational environment of man during this period. Man-environment relations are also examined.
APS
Keywords: charcoal; paleoecology; Portugal; vegetational environment

CHARCOAL ANALYSIS and the VEGETATIONAL EVOLUTION of NORTH-WEST PORTUGAL - FIGUEIRAL, I. (Oxford Journal of Archaeology, 1993)
Summary: The palaeoenvironment of north-west Portugal is investigated from the late Bronze Age to Roman times. This research is based on the analysis of charcoal from seven archaeological sites. the results contain important information for a better understanding of the vegetational environment of man during this period. Man-environment relations are also examined.
APSAPSThe following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: charcoal; paleoecology; Portugal; vegetational environment